The constrained court : law, politics, and the decisions justices make - Bailey, Michael A., 1969- (Princeton University Press, 2011)
How do Supreme Court justices decide their cases? Do they follow their policy preferences? Or are they constrained by the law and by other political actors? The Constrained Court combines new theoretical insights and extensive data analysis to show that law and politics together shape the behavior of justices on the Supreme Court. Michael Bailey and Forrest Maltzman show how two types of constraints have influenced the decision making of the modern Court. First, Bailey and Maltzman document that important legal doctrines, such as respect for precedents, have influenced every justice since 1950.